2018
DOI: 10.2174/1381612824666180926095709
|View full text |Cite
|
Sign up to set email alerts
|

Role of p53 Gene in Breast Cancer: Focus on Mutation Spectrum and Therapeutic Strategies

Abstract: TP53 is a tumor suppressor gene which is commonly mutated in various cancers including breast cancer. Alterations in the gene lead to an altered expression of various genes that are directly or indirectly under the transcriptional control of p53. This results in malfunctioning of DNA damage repair pathways, cell-cycle arrest, chromatin remodeling and apoptosis. Different mutations in TP53 gene have been reported in different ethnic groups and exon 4 and intron 3 are reported to be frequently mutated in breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 0 publications
2
81
0
Order By: Relevance
“…The present study identified the differentially expressed genes in mouse transcriptome data from the GEO database by comparing the low and normal expression levels of RNF8 in the TP53-mutant samples, revealing that downregulated genes were mainly enriched in several pathways involved in cell proliferation and apoptosis regulation, development and transcription regulation. This is consistent with previous studies (28,29), indicating that even in the presence of P53 mutations, the main function of RNF8 is still focused on the regulation of the cell cycle and transcription factors, thus confirming that the function of RNF8 is not completely P53-dependent and that TP53 mutations have a relatively small effect on the physiological function of RNF8.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study identified the differentially expressed genes in mouse transcriptome data from the GEO database by comparing the low and normal expression levels of RNF8 in the TP53-mutant samples, revealing that downregulated genes were mainly enriched in several pathways involved in cell proliferation and apoptosis regulation, development and transcription regulation. This is consistent with previous studies (28,29), indicating that even in the presence of P53 mutations, the main function of RNF8 is still focused on the regulation of the cell cycle and transcription factors, thus confirming that the function of RNF8 is not completely P53-dependent and that TP53 mutations have a relatively small effect on the physiological function of RNF8.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study has revealed that the function of RNF8 is highly dependent on the P53 protein, suggesting that RNF8 serves a biological role in synergy with P53 (27). However, numerous studies have revealed a number of mutations in the P53 gene in tumor cells (28,29); therefore, it is increasingly important to investigate the functional role of RNF8 under the condition of P53 mutation (27). The present study identified the differentially expressed genes in mouse transcriptome data from the GEO database by comparing the low and normal expression levels of RNF8 in the TP53-mutant samples, revealing that downregulated genes were mainly enriched in several pathways involved in cell proliferation and apoptosis regulation, development and transcription regulation.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the incidence of breast cancer differs among different populations around the world [ 1 ]. Over the past decades, major advances have been made in understanding the pathology of breast cancer at the molecular level, including the involvement of certain genes associated with the development of the disease such as BRCA1 , BRCA2 and P53 which produce tumor suppressor proteins and participate in damaged DNA repair [ 3 5 ]. P53 plays a key role in the regulation of cell proliferation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The present results also demonstrate that increased FAK protein expression correlates with a high Ki-67 expression level, thereby suggesting that elevated FAK expression promotes the proliferation of breast cancer cells. Kaur et al [ 44 ] have revealed that p53 also contributes to the pathogenesis of breast cancer via its roles in various cellular processes, including DNA damage repair, cell cycle arrest, and apoptosis. The present results demonstrate that enhanced FAK expression correlates with positive p53 status.…”
Section: Discussionmentioning
confidence: 99%